Frequency of high bleeding risk in patients undergoing percutaneous coronary intervention - Muhammad Muzaffar Mahmood; Farwa Eajaz; Aasif Hussain; Arva Zahid; Kiran Saeed; Junaid Rehman (Journal of the Pakistan Medical Association, 2021)
Objective: To assess the prevalence of risk factors for bleeding and high bleeding risk in patients undergoing percutaneous coronary intervention. Method: The single-centre retrospective observational study was conducted at ?? and comprised data of patients who underwent percutaneous coronary intervention from February 2018 to December 2019. Minor and major bleeding risk factors were identified on the basis of the consensus definition of the Academic Research Consortium. Patients with high bleeding risk were identified according to the consensus-based criteria of at least one major criterion or two minor criteria. Data was analysed using SPSS 20. Results: Of the 385 patients, 280(72.7%) were males. The overall mean age was 57.9+/-11.9 years. The indication of procedure was acute coronary syndrome in 367(95%) patients. Of all the patients, 171(45%) had bleeding risk, with 94(24%) patients having a high bleeding risk. Of these, 60(15.6%) patients had high risk based on the presence of at least one major criterion and 34(8.8%) patients because of the presence of two or more minor criteria. Patients with high bleeding risk were more likely to be older and female with more co-morbidities (p<0.05). Conclusion: Almost half of the patients undergoing percutaneous coronary intervention were found to have at least one bleeding risk factor, and one in four patients had high bleeding risk. Key Words: Haemorrhage, Dual antiplatelet therapy, Percutaneous coronary intervention. Continuous...